Enantiopure phosphonic acids as chiral inducers: homochiral crystallization of cobalt coordination polymers showing field-induced slow magnetization relaxation. Issue 42 (25th April 2016) - Feng, Jian-Shen; Ren, Min; Cai, Zhong-Sheng; Fan, Kun; Bao, Song-Song; Zheng, Li-Min
Abstract : Homochiral crystallization of ( M )- or ( P )-Co(SO4 )(1, 3-bbix)(H2 O)3 (1 M or1 P ) from an achiral precursor is achieved in the presence of a catalytic amount of ( S )- or ( R )-3-phenyl-2-((phosphonomethyl)amino) propanoic acid. Abstract : This Communication reports, for the first time, that enantiopure phosphonic acids can serve as chirality-inducing agents towards homochiral coordination polymers. Hence homochiral chain compounds ( M )- or ( P )-Co(SO4 )(1, 3-bbix)(H2 O)3 (1 M or1 P ) are obtained successfully using an achiral precursor of 1, 3-bis((1 H -benzo[ d ]imidazol-1-yl)methyl)benzene (1, 3-bbix) in the presence of a catalytic amount of ( S )- or ( R )-3-phenyl-2-((phosphonomethyl)amino)propanoic acid [( S )- or ( R )-2-ppapH3 ]. Furthermore, compound1 M provides the first example of homochiral cobalt compounds showing field-induced single ion magnet behavior.